An Introduction to the Thesis and Thesis Research in the Master of Archival Studies Program at the University of British Columbia - Eastwood, Terry (Archivaria, 2003)
In the introduction to the abstracts of archival studies theses, the author sets the context by assessing the experience of research in the Master of Archival Studies Program in the School of Library, Archival, and Information Studies at the University of British Columbia. He pays particular attention to the role of the thesis in creating a solid research base as well as helping the program to establish itself as a separate field of study in the university. RÉSUMÉ Dans cette introduction aux résumés des thèses en études archivistiques, l’auteur établit le contexte en évaluant l’expérience de recherche au sein du programme de maîtrise en études archivistiques de la « School of Library, Archival, and Information Studies » de l’Université de la Colombie-Britannique. Il porte une attention particulière au rôle joué par les thèses pour créer une solide base de recherche de même que pour aider le programme à s’établir comme un champ d’étude autonome au sein de l’université.